Analisis Dampak Dinamika Masyarakat Dan Kebudayaan Terhadap Perubahan Masyarakat Di Nagari Salayo Kabupaten Solok - Nadya Aurellia Rivenka; Lusi Adinda Miranti Putri; Lidya Rahmawati Amsah; Sisri Nauratul Ilmi; Tiara Amanda Saqira; Syamsir Syamsir (Jurnal Insan Pendidikan dan Sosial Humaniora, 2023)
This study aims to find out how the impact caused by the dynamics of society and culture on changes in the Nagari Salayo community, Solok Regency and what efforts can be made. This study uses qualitative research methods to make it easier for researchers to describe research in an open and in-depth manner regarding research problems. The research was conducted in Nagari Salayo, Solok Regency. The data sources studied by researchers used qualitative research methods based on positivism philosophy, as research informants namely the nagari guardian, the community and the parties involved. The research results obtained in this case the dynamics of society will continue to develop and grow over time. The process between humans and culture is an aspect that is interrelated so that the impact can be both positive and negative. Cultural changes in Nagari Salayo towards the lives of the surrounding community, namely where the existence of a new culture that collaborates with the old culture makes the community less culotte and people's thinking becomes more developed because the incoming culture is adjusted to the times and the old culture which previously existed in the village of Selayo. The efforts made by the people of Nagari Salayo are to continue to adapt according to the existing conditions.